Economic alternatives for growth, employment, and poverty reduction progressive policy recommendations for developing countries - McKinley, Terry. (Palgrave Macmillan, 2009)
"This book is a collection of working papers, policy briefs and training modules, published by the International Poverty Centre in Brazil, which provides a comprehensives set of recommendations for alternative economic policies that can generate growth, employment and poverty reduction in developing countries"--Provided by publisher.